The Knoxville Campaign : Burnside and Longstreet in east Tennessee - Hess, Earl J. (University of Tennessee Press, 2012)
"Hess's account of the understudied Knoxville Campaign sheds new light on the generalship of James Longstreet and Ambrose Burnside, as well as such lesser players as Micah Jenkins and Orlando Poe. Both scholars and general readers should welcome it. The scholarship is sound, the research, superb, the writing, excellent."--Steven E. Woodworth, author of Decision in the Heartland: The Civil War in the West In the fall and winter of 1863, Union General Ambrose Burnside and Confederate General James Longstreet vied for control of the city of Knoxville and with it the railroad that linked the Confederacy east and west. The generals and their men competed, too, for the hearts and minds of the people of East Tennessee. Often overshadowed by the fighting at Chickamauga and Chattanooga, this important campaign has never received a full scholarly treatment. In this landmark book, award-winning historian Earl J. Hess fills a gap in Civil War scholarship - a timely contribution that coincides with and commemorates the sesquicentennial of the Civil War The East Tennessee campaign was an important part of the war in the West. It brought the conflict to Knoxville in a devastating way, forcing the Union defenders to endure two weeks of siege in worsening winter conditions. The besieging Confederates suffered equally from supply shortages, while the civilian population was caught in the middle and the town itself suffered widespread destruction. The campaign culminated in the famed attack on Fort Sanders early on the morning of November 29, 1863. The bloody repulse of Longstreet's veterans that morning contributed significantly to the unraveling of Confederate hopes in the Western theater of operations. Hess's compelling account is filled with numerous maps and images that enhance the reader's understanding of this vital campaign that tested the heart of East Tennessee. The author's narrative and analysis will appeal to a broad audience, including general readers, seasoned scholars, and new students of Tennessee and Civil War history. The Knoxville Campaign will thoroughly reorient our view of the war as it played out in the mountains and valleys of East Tennessee. EARL J. HESS is Stewart W. McClelland Distinguished Professor in Humanities and an associate professor of history at Lincoln Memorial University. He is the author of nearly twenty books, including The Civil War in the West - Victory and Defeat from the Appalachians to the Mississippi and Lincoln Memorial University and the Shaping of Appalachia